Ethnographic Discourses on Women and Islam in Turkey - Onur, Petek. author. aut Link
X, 305 p. 590 illus.
Keywords: This book provides a meta-reading of how ethnographic discourses on women and Islam in Turkey have changed since their emergence in 1983. It analyses the published ethnographic works in three discursive periods and shows that paradigm shifts in social sciences, processes of neo-liberal globalization and globalization of Islamism as well as political, social, cultural and economic transformations at the local level shape these periods. As an exceptional example of modernization in the Middle East and the post-imperial states in South-East Europe, Turkey has been experiencing tensions between Islamic beliefs and practices and Westernization and secularization processes. Countless aspects of Muslim women’s lives appear as symbols and indicators in this society like in many other Muslim majority societies and to scholars of gender and women’s studies in discussing the faith-based patriarchy. Thus, this book exhibits the necessity of developing a critical perspective on ethnographic representations of Muslim women in Turkey. Petek Onur is an assistant professor at University of Copenhagen, Department of Cross-Cultural and Regional Studies. She was a Marie-Curie fellow at the same department in 2020-2022 and postdoctoral researcher at Europa-Universität Flensburg, Interdisciplinary Centre for European Studies in 2023-2024. .